NCAA e-sports 20XX: an analysis of radical innovation adoption through firm collaboration. (5th April 2021) - Williams, Dylan; Tutka, Patrick; Gawrysiak, Joey; Jenny, Seth
The National Collegiate Athletic Association (NCAA) is considering the adoption of e-sports (i.e., organised competitive video gaming), which could be considered a radical innovation as it deviates in many areas from traditional sports (e.g., online game play format, lack of high physical exertion, complicated intellectual property rights for each game, etc.). However, collaboration with firms familiar with the innovation (e.g., National Association of Collegiate eSports - NACE) might mitigate risks surrounding the radical innovation. Thus, the purpose of this paper was to investigate whether a potential association between the NCAA and NACE would be advantageous to both organisations. Through a deductive qualitative content analysis underpinned by Rogers's (2003) innovation characteristics (e.g., complexity, compatibility and relative advantage), several themes emerged: physical exertion, e-sports structure, amateurism, eligibility, compensation, profitability, and diversity and gender equity. These themes are discussed while identifying the benefits and issues surrounding a NCAA/NACE collegiate e-sports adoption and collaboration.